In silico network pharmacology and in vivo analysis of berberine-related mechanisms against type 2 diabetes mellitus and its complications. (10th August 2021) - Di, Sha; Han, Lin; An, Xuedong; Kong, Ran; Gao, Zezheng; Yang, Yingying; Wang, Xinmiao; Zhang, Pei; Ding, Qiyou; Wu, Haoran; Wang, Han; Zhao, Linhua; et al.
Abstract: Ethnopharmacological relevance: Berberine (BBR), extracted from the traditional medicinal plant Coptis chinensis Franch., has been widely used for the treatment of type 2 diabetes mellitus (T2DM) and its complications. Aim of the study: To determine the potential pharmacological mechanisms underlying BBR therapeutic effect on T2DM and its complications by in silico network pharmacology and experimental in vivo validation. Materials and methods: A predictive network depicting the relationship between BBR and T2DM was designed based on information collected from several databases, namely STITCH, CHEMBL, PharmMapper, TTD, Drugbank, and PharmGKB. Identified overlapping targets related to both BBR and T2DM were crossed with information on biological processes (BPs) and molecular/signaling pathways using the DAVID platform and Cytoscape software. Three candidate targets identified with the BBR–T2DM network (RXRA, KCNQ1 and NR3C1) were evaluated in the C57BL/6J mouse model of T2DM. The mice were treated with BBR or metformin for 10 weeks. Weight, fasting blood glucose (FBG), oral glucose tolerance, and expression levels of the three targets were evaluated. Results: A total of 31 targets of BBR that were also related to T2DM were identified, of which 14 had already been reported in previous studies. Furthermore, these 31 overlapping targets were enriched in 21 related BPs and 18 pathways involved in T2DM treatment. The identified BP-target-pathway network revealed the underlying mechanisms of BBR antidiabetic activity were mediated by core targets such as RXRA, KCNQ1, and NR3C1. In vivo experiments further confirmed that treatment with BBR significantly reduced weight and FBG and alleviated insulin resistance in T2DM mice. Moreover, BBR treatment promoted RXRA expression, whereas it reduced KCNQ1 and NR3C1 expression in the liver. Conclusion: Using network pharmacology and a T2DM mouse model, this study revealed that BBR can effectively prevent T2DM symptoms through vital targets and multiple signaling pathways. Network pharmacology provides an efficient, time-saving approach for therapeutic research and the development of new drugs.